The Effect of Relationship Quality on Loyalty with Customer Retention as an Intervening Variable for PT. Bank BTN Malang Sharia Branch - Putri, Aldila Nur Rafika; Rahayu, Yayuk Sri (Universitas Mercu Buana, 2023)
Competence which the more this demand increases every so that banks are capable of competing, maintaining and guarding customer loyalty. Wrong one strategy which needed for Thing the is strategy Relationship Quality . This study was conducted to know the influence of Relationship Quality facing customer loyalty. This study was conducted to customers of PT. Bank BTN Branch Sharia Poor with use sampling technique. The sample size taken is as much as 100 respondents. This study consists of three variables which are the free variable (X) which is connection quality (Relationships Quality), bound variable (Y) which is customer loyalty, and intervention variable (Z) which is customer retention . The data collected use a questionnaire and then the data is processed using an analysis description and analysis of the SEM-PLS.